Longitudinal melanonychia in a child. - Milano, A. (European Journal of Pediatric Dermatology, 2019)
Longitudinal melanonychia (LM) may be benign (melanocytic hyperfunction, lentigo, nevus) or malignant (melanoma). In the Caucasian prepubertal child the nevus is the most frequent benign cause of LM. There are 12 (1) cases of nail melanoma in the prepubertal age in the world literature; they are all melanoma in situ and many Authors have doubts about the diagnosis. The clinical criteria useful to differentiate in adults benign from malignant LM - band width, irregular bands, rapid growth, involvement of nail folds, nail dystrophy - are not valid in the child. The biopsy of the matrix, which is more difficult to perform in the child and associated with permanent residua, is not always decisive even with the most reliable techniques such as fluorescence in situ hybridization (FISH). For these reasons, most Authors (2) recommend behaving for the child’s LM as one behaves with melanocytic skin nevi in pediatric age.